Developing Immersive Augmented Reality Applications on Spatial Geometry Materials for Junior High School Slow Learners - Rilend Putri, Khairina Aqilah; Pamuji,; Masitoh, Siti (Jurnal Paedagogy, 2026)
This study aims to describe the development process and outcomes of an interactive mobile application called KURA AR as an assistive mathematics technology for slow learners. Adopting the systematic ADDIE development model, this study employed a quantitative descriptive design with a small-group trial involving five ninth-grade slow learners at SMPN 2 Sukodono using a One-Group Pretest–Posttest Design. The research instruments used a five-point Likert scale to evaluate the validity and practicality of the developed application. Quantitative data obtained from validation sheets were analyzed using descriptive percentage analysis based on the five-point Likert scale criteria. The expert validation results demonstrated a high level of feasibility, with scores of 80% from the material expert and 100% from the media expert. The field implementation results indicated that the application had high usability, achieving a teacher practicality score of 93% with a total score of 326 out of 350, supported by highly positive responses from students. Furthermore, the effectiveness test revealed a significant improvement in students’ learning outcomes, with the mean score increasing from 38 in the pretest to 90 in the posttest. The normalized gain (N-Gain) analysis using Hake’s formula produced an average score of 0.83, which was categorized as high effectiveness. In conclusion, the developed KURA AR mobile application is valid, practical, and effective in supporting spatial visualization and improving geometry learning outcomes among junior high school students with slow learning difficulties.